1988
DOI: 10.1083/jcb.107.6.2657
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of kinesin-driven microtubule motility by monoclonal antibodies to kinesin heavy chains.

Abstract: Abstract, We have prepared and characterized seven mouse monoclonal antibodies (SUK 1-7) to the 130-kD heavy chain of sea urchin egg kinesin. On immunoblots, SUK 3 and SUK 4 cross-reacted with Drosophila embryo ll6-kD heavy chains, and SUK 4, SUK 5, SUK 6, and SUK 7 bound to the 120-kD heavy chains of bovine brain kinesin. Three out of seven monoclonal antikinesins (SUK 4, SUK 6, and SUK 7) caused a dose-dependent inhibition of sea urchin egg kinesininduced microtubule translocation, whereas the other four mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
153
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(156 citation statements)
references
References 35 publications
3
153
0
Order By: Relevance
“…8A), suggesting that a large proportion of these proteins are soluble. This pattern corresponded to that seen with the monoclonal antibody, Suk4 (42), that recognizes both uKHC and nKHC. However, when probed with an antibody against synaptophysin (Boehringer Mannheim), the pattern was different.…”
Section: Figmentioning
confidence: 81%
See 1 more Smart Citation
“…8A), suggesting that a large proportion of these proteins are soluble. This pattern corresponded to that seen with the monoclonal antibody, Suk4 (42), that recognizes both uKHC and nKHC. However, when probed with an antibody against synaptophysin (Boehringer Mannheim), the pattern was different.…”
Section: Figmentioning
confidence: 81%
“…Western blotting was done as described above. Anti-synaptophysin (Boehringer Mannheim) and Suk4 (42) antibodies were used at a 1:10 dilution of the manufacturer's stock solution and 1:10 dilution of hybridoma supernatant, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…An antibody to the heavy chain of conventional kinesin, SUK4 (Ingold et al, 1988), showed no reactivity in the NF preparation by Western blotting ( Figure 6A) or immuno-EM ( Figure 5G), although reactivity is observed with intermediate fractions resulting from the NF preparation ( Figure 6A). The absence of conventional kinesin, the most prevalent form of kinesin, in the purified NF fraction precludes the possibility of contamination by motor-bound organelles and nonspecific interactions between NFs and soluble kinesins.…”
Section: A Number Of Kinesin-like Proteins Copurify With Nfsmentioning
confidence: 99%
“…With a broadspecificity kinesin antibody, anti-HIPYR (Sawin et al, 1992), a set of candidate proteins have been identified each of which may or may not contribute to the motility observed. Of the NF-associated kinesins identified by the HIPYR antibody, the 110-kDa polypeptide detected by the anti-HIPYR antibody does not correspond to the conventional kinesin isoform (kinesin-I) recognized by the SUK4 antibody (Ingold et al, 1988) (Figure 5A). The 110-kDa kinesin-like protein may, however, represent one of the other KIF5/kinesin-I isoforms (Nakagawa et al, 1997) of which two, KIF5A and KIF5C, are restricted to neural tissue.…”
Section: Kinesin-related Proteins Copurify With Nfsmentioning
confidence: 99%
“…In the present study, RNAi was used alone or combined with the expression of a dominant-negative construct of the mouse kinesin-1 light chain 2 tetratricopeptide domain (KLC-TPR) to compete out the cargo-binding domain of the endogenous motor (16). Alternatively, microinjection of the Suk-4 antibody was used to block acutely kinesin movement on microtubules (23). To measure polymerization rates, we followed fluorescent EB1 or CLIP-170 in time-lapse experiments.…”
Section: Kinesin-1 Inhibition Slowsmentioning
confidence: 99%